Pemberdayaan Siswa Youth Entrepreneurs melalui Pemanfaatan Limbah Pertanian di SMAN 1 Tenjo - Ambar Susanti (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
The implementation of Community Service Empowering Students as youth entrepreneurs through the utilization of agricultural waste potential at SMAN 1 Tenjo, Bogor Regency aims to: 1) provide knowledge related to the utilization of agricultural waste and its environment, 2) increase student interest in developing the utilization of agricultural waste and its environment into economic value. The expected output in this activity is that students can utilize agricultural waste and its scope into economic value, and play a role in maintaining the school environment. Implementation on 20-21 October 2024 at SMAN 1 Tenjo, and continued on 26-27 October online. The activity partner is the Disaster Safe Education Task Force of SMAN 1 Tenjo, through one of the programs, namely waste mitigation in the school environment. The members of the task force total 20 people. The team consists of lecturers and students from the Faculty of Agriculture, KH.A. Wahab Hasbullah University (UNWAHA). The methods used are lectures, discussions, and practices. The results of the Student Empowerment activity as youth entrepreneurs through the utilization of agricultural waste potential at SMAN 1 Tenjo Bogor, are; 1) there was an increase in the percentage of participants around 55,72% related to understanding the material, 2) generally participants were very satisfied (65%) with the material and training provided, and 3) the implementation of the activity was a follow-up to the cooperation between the two parties and motivated the training participants as young entrepreneurs, increased their love for agriculture, and played a role in protecting their environment.